Female University Students and Fintech Literacy: Evidence from Somalia - Abdulle, Mohamed Abdirahman; Kulmie, Dayah Abdi; Awale, Abdirahman Abdinur; Ibrahim, Mohamed Salad; Adan, Abdullahi Tahlil (International Journal of Economics and Financial Issues, 2025)
Fintech, a field encompassing digital banking, payments, and investment management, has revolutionized financial services by making them more accessible, convenient, and efficient. The growth of Fintech is driven by advanced technologies such as blockchain, IoT, AI, and robo-advisors, while also posing challenges for regulators and market participants. Fintech research is essential for driving innovation, shaping the future of finance, and addressing emerging challenges. This study examines the awareness and knowledge of Fintech concepts among female university students in Somalia. Using a quantitative cross-sectional research design, 92 students from four universities were surveyed to assess their familiarity with key Fintech topics, including blockchain, smart contracts, neo-banking, and cloud computing. The findings reveal significant gaps in Fintech literacy, with a majority of students showing limited awareness of emerging technologies. While 63% of students expressed the need for a dedicated Fintech course, only 32.6% felt adequately prepared for the Fintech industry. Regression analysis indicated that a student’s major significantly influences their Fintech knowledge. The study highlights the need for curriculum reform and improved resources to enhance Fintech education in Somalia.